Cost of dementia and the relationship between stage of dementia and cost of care in Greece. Issue 6 (2nd June 2020) - Tsampalas, Evangelos; Aravantinou-Fatorou, Konstantina; Karakatsani, Eleutheria; Karantali, Eleni; Leontiou, Lili; Anastasiou, Athanasios
Abstract : Objective: The current study attempts to estimate the cost of dementia in relation to the severity of the disease in Greece. Methods: A prospective observational study was conducted in Tripoli, Arcadia at the neurological clinic of a secondary hospital. The study included 110 patients and their main caregivers. The total cost of dementia has been calculated as well as its allocation to private and public funding. The results were correlated with three stages of disease severity (mild–moderate–severe) with a multivariate regression model. Results: The average total cost of caring for dementia is €819.89 per month: €710.60 of this is the private cost and €109.29 is the public cost. The cost is positively correlated statistically with the progress of the disease in the three stages of severity. Conclusions: The cost of caring for people with dementia in the authors' research appears lower than that in developed Western societies and in relation to other developing societies. The Greek economic crisis seems to be a determining factor in this result. However, it is still a high cost, which is mainly paid by the patient and the family.